Utilization of Low-quality Bentonite in Landfill Liners - Ahmed Hosny Abdel-Rahman; Mahmoud Fawzy Awad-Allah; Khaled Mamdoh (Lowland Technology International, 2021)
Researchers are usually working not only on finding new alternatives for landfill lining which achieve environmental standards but also the low-cost solution is one of the important goals. The main objective of this paper is to introduce landfill liner materials that satisfy the standards and meanwhile represent economic solutions for this environmental problem. Extensive experimental tests were conducted on ten mixes of bentonites including: Atterberg limits, compaction curves, and falling head permeability tests. Moreover, field test was conducted to measure the permeability of the designed LQB mix using the double ring infiltrometer. Bentonite-sand mixes are consisted of two different materials in terms of grain size, permeability, chemical activity, and strength. The paper results indicated that if they combined in their optimum proportions, they succeeded in forming an excellent seepage barrier. The results have proven that the use of LQB instead of the HQB can achieve the required standards of the environmental protection agencies.